Redistribution of responsibility? Fire safety education as a strategy for futureproofing volunteer firefighters - Brad, Alexandru; Adam Hernández, Alistair; Steinführer, Annett (Raumforschung und Raumordnung | Spatial Research and Planning, 2024)
Volunteer firefighters are an established institution in many rural areas across Europe. In spite of this ubiquity, many volunteer brigades have been increasingly facing challenges in discharging their functions. Issues such as undertaking necessary investments, and ensuring daytime availability have become particularly critical against the backdrop of an increase in the number of interventions. Many of the measures intended to futureproof volunteer firefighting are based on transferring responsibility to different actors. To this end developing and expanding the reach of fire safety education functions to enhance the public’s prevention and self-protection skills. The aim of this paper is to explore the process of institutional change induced by innovative initiatives, which aim to advance fire safety education. For the study, we draw on empirical research, which follows the development and mainstreaming of two projects in Austria and Germany. These initiatives aim to standardise disparate approaches and are underpinned by new forms of multi-level cooperation. Our inductive analysis identifies five key steps which define the successful long-term implementation of projects in coproduced services of general interest. We conclude with observations on the redistribution of responsibility for fire services and hazard prevention in contemporary societies.